Using Zinc Oxide Nanoparticles to Improve the Color and Berry Quality of Table Grapes Cv. Crimson Seedless - Mohamed K. Abou El-Nasr; Hussein M. El-Hennawy; Mina S. F. Samaan; Taher A. Salaheldin; Ahmed Abou El-Yazied; Ashraf El-Kereamy (Plants, 2021)
Producing high-quality table grapes is becoming a challenge in the warmer area of the world due to the global increase in temperature, which negatively affects anthocyanin biosynthesis and other fruit quality attributes. Nanotechnology is a growing field that can be a very useful tool to improve crop productivity and sustainability. The red color is one of the major fruit quality parameters that determine table grape marketability. This study aimed to investigate the role of the zinc element in improving the marketable characteristics of Crimson seedless (Vitis vinifera L.) table grape berries i.e., color, firmness, total soluble solids and sugars; besides its role in activating PAL and SOD enzymatic systems. Additionally, this paper investigated the additive advantages of zinc when applied in nanometric form. Five concentrations of zinc oxide nanoparticles, ZnO NPs (0, 25, 50, 100 and 250 ppm), were compared to zinc oxide in mineral form at a concentration of 250 ppm to investigate their effects on the marketable characteristics of Crimson seedless grape cultivar. The treatments were applied as foliar spray on three-year-old Crimson seedless vines grafted on Richter 110 rootstock grown in one of the major table grape production area in Egypt. The experiment was arranged in completely randomized block design and each vine was sprayed with five letters of the solution. The use of the lowest concentration (25 ppm) of ZnO NPs achieved the highest significant enzyme activity (PAL and SOD). Moreover, the T.S.S, sugars and anthocyanin content in berries increased significantly in association of decreasing acidity. On the other hand, the use of a 50 ppm concentration led to an increase in fruit firmness. Collectively, our data showed that 25 ppm of zinc nanoparticles improved PAL and SOD enzymes activity, improved red coloration in table grape and was more effective than the 250 ppm zinc oxide mineral form.